The Lineage Status of the Child Born from Zina: A Comparative Analysis of Islamic Law and Indonesian Positive Law - Santika, Sovia; Musthafa, Halum; Hasibuan, Marzuki Hafiz Alhamdani (Fakultas Syariah IAIN Madura, 2025)
The development of the times and the influence of Western culture have altered the patterns of behavior in society, particularly among the younger generation, who increasingly neglect lega l norms and religious values. One of the impacts of this change is the rise in cases of extramarital sexual relations, which give rise to social and legal issues, especially concerning the status and position of children born from zina. This study aims to examine in depth the lineage status (nasab) of children born from zina on the perspective of Islamic law and Indonesia's positive law, with a focus on the dynamics following the controversial Constitutional Court Decision No. 46/PUU-VIII/2010 regarding the recognition of the status of such children. The research method used is library research with a qualitative descriptive approach, in which data were obtained from various sources such as books, scholarly journals, legislation, and court decision documents. The findings show a significant difference between Islamic law and positive law regarding the status of children born form zina. Islamic law explicitly states that such a child only has a lineage relationship with the mother and her family, without any rights to inheritance, financial support, or guardianship from the biological father. Meanwhile, Indonesian positive law, particularly after the Constitutional Court’s ruling, allows for the recognition of civil relationships between a child born out of wedlock and the biological father through legal channels, which carries implications for inheritance rights, financial support, and legal status. This study argues that the decision is not in line with the principles of Islamic teachings and potentially undermines the sanctity of the institution of marriage. Therefore, a regulation is needed that can bridge the interests of positive law and the values of sharia.